Effects of Menopause in Women With Multiple Sclerosis: An Evidence-Based Review - Bove, Riley; Okai, Annette; Houtchens, Maria; Elias-Hamp, Birte; Lugaresi, Alessandra; Hellwig, Kerstin; Kubala Havrdová, Eva (Frontiers in Neurology, 2021)
Over two thirds of all individuals who develop multiple sclerosis (MS) will be women prior to the age of menopause. Further, an estimated 30% of the current MS population consists of peri- or postmenopausal women. The presence of MS does not appear to influence age of menopausal onset. In clinical practice, symptoms of MS and menopause can frequently overlap, including disturbances in cognition, mood, sleep, and bladder function, which can create challenges in ascertaining the likely cause of symptoms to be treated. A holistic and comprehensive approach to address these common physical and psychological changes is often suggested to patients during menopause. Although some studies have suggested that women with MS experience reduced relapse rates and increased disability progression post menopause, the data are not consistent enough for firm conclusions to be drawn. Mechanisms through which postmenopausal women with MS may experience disability progression include neuroinflammation and neurodegeneration from age-associated phenomena such as immunosenescence and inflammaging. Additional effects are likely to result from reduced levels of estrogen, which affects MS disease course. Following early retrospective studies of women with MS receiving steroid hormones, more recent interventional trials of exogenous hormone use, albeit as oral contraceptive, have provided some indications of potential benefit on MS outcomes. This review summarizes current research on the effects of menopause in women with MS, including the psychological impact and symptoms of menopause on disease worsening, and the treatment options. Finally, we highlight the need for more inclusion of MS patients from underrepresented racial and geographic groups in clinical trials, including among menopausal women.